2022
DOI: 10.1101/2022.09.03.506476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined blockade of VEGF, Angiopoietin-2, and PD1 reprograms glioblastoma endothelial cells into quasi-antigen-presenting cells

Abstract: Glioblastoma (GBM) remains a highly aggressive and uniformly fatal primary tumor, which resists cytotoxic, targeted, antiangiogenic, and immune therapies, even when used in combination. Here we report that tumor endothelial cell dysfunction confers resistance to immunotherapy in preclinical GBM models. Anti-VEGF-therapy-induced vascular normalization is insufficient to fully restore the endothelial cell function. Strikingly, concomitant blockade of Ang2, VEGF, and PD1 reprograms dysfunctional endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…In addition to immune suppression, Tregs expressing VEGFRs, such as neurophilin-1 mediated angiogenesis and anti-VEGF mAb, can lead to Tregs depletion and enhance the immunologically beneficial effects in the TME. VEGF also suppresses DC maturation and upregulates the expression of PD-L1 on DC and PD-1 and CTLA-4 on T cells, leading to T-cell exhaustion and suppression of their function, resulting in immunosuppression ( 57 ) ( Figure 1A ). Therefore, targeting VEGF/VEGFR-enhanced anti-tumor immunity and tumor cell elimination.…”
Section: Normalizing Tumor Vasculature Improves Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to immune suppression, Tregs expressing VEGFRs, such as neurophilin-1 mediated angiogenesis and anti-VEGF mAb, can lead to Tregs depletion and enhance the immunologically beneficial effects in the TME. VEGF also suppresses DC maturation and upregulates the expression of PD-L1 on DC and PD-1 and CTLA-4 on T cells, leading to T-cell exhaustion and suppression of their function, resulting in immunosuppression ( 57 ) ( Figure 1A ). Therefore, targeting VEGF/VEGFR-enhanced anti-tumor immunity and tumor cell elimination.…”
Section: Normalizing Tumor Vasculature Improves Cancer Immunotherapymentioning
confidence: 99%
“…Moreover, proangiogenic signaling induced by angiopoietin 2 (ANG2)/TIE2 cytokines contributes to vascular VEGF-dependent angiogenesis and increases microvessel density of the TME as well as vascular permeability, and thus, dual targeting of ANG2 and TIE2 or ANG2 and VEGF extends both the window of normalization and reduces metastatic dissemination in patients with glioblastoma compared with VEGF or ANG2 inhibition alone ( 39 , 59 ). Depending on the cell source, IFNγ produced by T cells limits the tumor angiogenesis ( 54 ), while IFNγ-expressing ECs upregulate PD-L1 in tumor cells and limit antitumor immunity, which guided that multi-targeting of ANG2, VEGF, and PD-L1 enhanced antitumor responses in transplanted tumor models ( 57 , 60 ). Like IFNγ, the anti–VEGF-ANG2 antibody upregulates immune inhibitory molecules such as PD-L1 on both ECs and tumor cells to promote T-cell exhaustion, highlighting the benefit of co-treatment with anti–PD-1 antibody ( 61 ).…”
Section: Normalizing Tumor Vasculature Improves Cancer Immunotherapymentioning
confidence: 99%
“…For instance, resistance to α-VEGF monotherapy was common in glioblastoma. A new study reported that combined blockade of VEGF, Angiopoietin-2, and PD1 could reprogram glioblastoma endothelial cells into quasi-antigen-presenting cells and induced a durable anti-tumor T cell response [ 166 ] . A recent review has nicely summarized the current status of combinatorial approaches, including both chemo- and immunotherapies, for glioblastoma treatment [ 167 ] .…”
Section: Opportunitiesmentioning
confidence: 99%
“…This may be because the site is immunologically privileged and the vasculature defining the blood–brain barrier (BBB) is unique. Further, this could be due to an abundance of Treg cells, the high expression of Ang-2, and cerebral edema [ 175 , 176 , 177 ]. GBM is infiltrative in nature, and the location of the residual tumor (after surgery) is typically unreachable for chemotherapies and therapeutic antibodies (such as targeted anti-VEGF antibodies) because of the BBB [ 178 ].…”
Section: Anti-cancer Treatments That Engender Tumor Vascular Normaliz...mentioning
confidence: 99%